Sugar as a genetic light switch: a sucrose-inducible expression system in Aspergillus niger - Plath, Bella, author; Khakhar, Arjun, advisor; Moss, Dylan, committee member (Colorado State University. Libraries, 2026)
Mold is often condemned for its unwanted growth, such as on a cucumber in a lunchbox, in the corner of a shower, or in houseplant soil. However, this ability of mold to grow in a wide variety of environments makes it a powerful tool in modern biotechnology. Mold, or filamentous fungi, has diverse metabolite production which allows it to adapt to its surroundings. This capacity to express a vast range of products and stable growth makes it an ideal organism for large-scale production of metabolites. The filamentous fungi Aspergillus niger, specifically, produces an abundance of useful organic acids, enzymes, and proteins. The purpose of this research is to identify a method for increased yield of these target metabolites while also increasing the sustainability of the biofermentation process as a whole. The approach was implementing sucrose-inducible expression of target genes. In the presence of sucrose, A. Niger could increase yield of target metabolites. Additionally, the sucrose could induce morphological changes that cause the fungi to grow around a sucrose-producing cyanobacteria, creating a lichen-mimicking system. This system could drastically decrease the inputs needed for biofermentation, increasing process sustainability. This research works to confirm the ability of a sucrose-inducible promoter (PfopA) by increasing expression of a fluorescence protein in sucrose media. Using gene editing and fluorescence microscopy, this experiment demonstrated sucrose-inducible promotion of a target protein under sucrose culture conditions without compromising growth of the fungi. This knowledge suggests promising potential for gene editing techniques to increase A. niger production as well as creation of a synthetic lichen system for fungal production. These further developments would substantially improve sustainability and cost in current biofermentation industrial production processes.
Keywords: Honors Thesis